Kebijakan Kriminal terhadap Tindak Pidana Berbasis Gender dalam Kuhp Baru: Evaluasi Pasal tentang Kekerasan Seksual dan Kekerasan Psikis - Ahmad Senang; Budi Sastra Panjaitan; Arifuddin Muda Harahap (Pusat Riset dan Inovasi Nasional, 2025)
The ratification of the new Criminal Code (KUHP) through Law Number 1 of 2023 marks an important milestone in the history of Indonesian criminal law. The new Criminal Code replaces the colonial product that has been in place for more than a century and brings significant updates, especially in the regulation of gender-based crimes such as sexual and psychological violence. The recognition of these forms of violence is a response to the demands of civil society and is part of Indonesia's commitment to international human rights instruments. However, the effectiveness of such arrangements still faces serious challenges, such as the narrowness of the criminal formulation, the high burden of proof, and the potential for gender bias in the criminal justice system. In this context, criminal law should not only be a means of repression, but also carry out preventive and protective functions through holistic criminal policies. An integrative approach that combines penal and non-penal strategies is important to address the complexity of gender-based violence that is structural and multidimensional. This article aims to critically evaluate the provisions of the new Criminal Code related to sexual and psychological violence in the perspective of gender-responsive criminal policy. The evaluation was carried out taking into account the principles of restorative justice, the protection of victims' rights, and the need for social transformation that supports equality and non-discrimination. The results of this study are expected to be an input for the improvement of a criminal law system that is fairer and on the side of victims, especially women and other vulnerable groups.